Monitoring of the load-induced RC beam structural tension/compression stress and damage using piezoelectric transducers. (1st January 2018) - Ai, Demi; Luo, Hui; Wang, Chao; Zhu, Hongping
Highlights: Effect of structural tension/compression stress was incorporated into the impedance model. Experiment on a RC beam subjected to a four-point bending test till failure was conducted. Development of structural tension/compression stress was monitored using PZT transducers. Characters of EMA signatures were mathematically correlated to tension/compression stress. Quantification of stress and damage were analyzed using statistical index. Abstract: Efficacious monitoring the mechanical stress of engineering structures or components holds the key to understanding the occurrence of structural damage in Structural Health Monitoring (SHM) domains. This paper investigated the monitoring of the load-induced structural tension/compression stress and damage using smart Piezoelectric lead Zirconate Titanate (PZT) transducers mounted to specific locus on structures. Structural tension/compression stress was theoretically incorporated into mechanical impedance to formulate a novel one-dimensional PZT-structure dynamic interaction model. Proof-of-concept experimentation was conducted using a reinforced concrete (RC) beam subjected to a four-point bending test till failure, in which tension and compression stress were simultaneously produced at the bottom/top edge of the beam and captured by two mounted PZT transducers. Load-induced structural tension/compression stress and stress-induced damage were qualitatively evaluated through analyzing the characters of electromechanical admittance (EMA) signatures and comparing to that of the non-stressed PZT transducer. Quantification assessment of stress and damage using statistical root mean square deviation index were also presented. Test results indicated that the peak variation and frequency shift of EMA signatures responding to tension and compression stress were converse in nature, and their gradual changes provided cogent evidences for predicting the development of stress and damage. Results of this paper can be potentially to help monitor structural stress and discriminate from damages in real-life SHM applications.